Growth and Structural Characterization of PbTe/PbEuTe Double Barrier - A.M.P. dos Anjos (Brazilian Journal of Physics, 2006)
A series of PbTe/PbEuTe double barrier samples with different barrier widths were successfully grown onBaF2 substrates by molecular beam epitaxy. The electron concentration of PbTe spacer and well layers wascontrolled by the deviation from stoichiometry, while the buffer and cap layers were intentionally doped withbismuth to obtain low-resistivity layers to be used as top and bottom contacts. Assuming 50% of band offset, abarrier height of 150 meV was determined by infrared transmission measurements, corresponding to a PbEuTebarrier with 5% of europium content. The structural parameters of the samples were accurately determinedby combining the measurement in a high-resolution x-ray diffractometer in the triple-axis configuration with asimulation within the framework of dynamical theory of diffraction.A series of PbTe/PbEuTe double barrier samples with different barrier widths were successfullygrown on BaF2 substrates by molecular beam epitaxy. The electron concentration of PbTe spacerand well layers was controlled by the deviation from stoichiometry, while the buffer and cap layerwere intentionally doped with bismuth to obtain low-resistivity layers to be used as top and bottomcontacts. Assuming 50% of band offset, a barrier height of 150 meV was determined by infraredtransmission measurements, corresponding to a PbEuTe barrier with 5% of europium content. Thestructural parameters of the samples were accurately determined by combining the measurement ina high-resolution x-ray diffractometer in the triple-axis configuration with a simulation within theframework of dynamical theory of diffraction.